2000
DOI: 10.1152/jn.2000.84.3.1677
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation Disrupts Eye-Hand Interactions in the Posterior Parietal Cortex

Abstract: Recent neurophysiological studies have started to shed some light on the cortical areas that contribute to eye-hand coordination. In the present study we investigated the role of the posterior parietal cortex (PPC) in this process in normal, healthy subjects. This was accomplished by delivering single pulses of transcranial magnetic stimulation (TMS) over the PPC to transiently disrupt the putative contribution of this area to the processing of information related to eye-hand coordination. Subjects made open-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 19 publications
4
23
0
1
Order By: Relevance
“…Wilmut et al [34] tested the effect of producing saccades on the accuracy of sequential pointing and concluded that the role of ocular proprioception was far less important than the role of the feedforward system that is activated when an eye movement is initiated. Van Donkelaar et al [35] provided even more direct evidence. The influence of decorrelating eye and hand movement start points (see Section 1) on hand movement amplitude is significantly reduced by transcranial magnetic stimulation over the posterior parietal cortex when stimulation is delivered 0-100 ms prior to saccade onset.…”
Section: Discussionmentioning
confidence: 97%
“…Wilmut et al [34] tested the effect of producing saccades on the accuracy of sequential pointing and concluded that the role of ocular proprioception was far less important than the role of the feedforward system that is activated when an eye movement is initiated. Van Donkelaar et al [35] provided even more direct evidence. The influence of decorrelating eye and hand movement start points (see Section 1) on hand movement amplitude is significantly reduced by transcranial magnetic stimulation over the posterior parietal cortex when stimulation is delivered 0-100 ms prior to saccade onset.…”
Section: Discussionmentioning
confidence: 97%
“…Three-dimensional rendering of a typical subject's structural MRI with marked cortical sites in left (red symbols) and right (blue symbols) hemispheres: square, SPOC; circle, mIPS; triangle, AG (dorsal-lateral view). Both the mIPS (Sereno et al, 2001;Medendorp et al, 2003Medendorp et al, , 2005Merriam et al, 2003;Prado et al, 2005;Schluppeck, 2005;Schluppeck et al, 2006;Beurze et al, 2007Beurze et al, , 2009Fernandez-Ruiz et al, 2007;Hagler et al, 2007;Levy et al, 2007;Zettel et al, 2007;Tosoni et al, 2008) and SPOC (Astafiev et al, 2003;Connolly et al, 2003;Prado et al, 2005;Fernandez-Ruiz et al, 2007;Zettel et al, 2007;Culham et al, 2008;Tosoni et al, 2008;Beurze et al, 2009;Filimon et al, 2009;Gallivan et al, 2009) are regions derived from previous fMRI studies, whereas the AG corresponds to EEG coordinates P3 and P4, which have been used in many previous TMS studies for saccade and reach, including ours (Elkington et al, 1992;Müri et al, 1996Müri et al, , 2000van Donkelaar et al, 2000van Donkelaar et al, , 2002Kapoula et al, 2001;Smyrnis et al, 2003;Nyffeler et al, 2005;van Donkelaar and Adams, 2005;Vesia et al, 2006Vesia et al, , 2008Koch et al, 2008). The latter was included here to relate current results to previous TMS studies.…”
Section: Methodsmentioning
confidence: 99%
“…Note that foci were based on reported Talairach coordinates transformed to surface locations on a subject's pial surface and represent averaged group peaks of activity, lesion overlap, and stimulation area [shaded orange area, intraparietal sulcus; shaded magenta area, parieto-occipital sulcus; dotted white line, temporal occipital sulcus (TOS)]. fMRI activation, lesion foci, and TMS sites are as follows: for saccade, 1 (Sereno et al, 2001;Merriam et al, 2003), 8 (Schluppeck, 2005Schluppeck et al, 2006), P4 (Elkington et al, 1992;Müri et al, 1996Müri et al, , 2000Kapoula et al, 2001;Yang and Kapoula, 2004;Nyffeler et al, 2005); for saccade and reach, 8 (Levy et al, 2007), 19 (Beurze et al, 2009); for saccade and point, 3 (Medendorp et al, 2003), 7 (Zettel et al, 2007), 10 (Hagler et al, 2007), 11 (FernandezRuiz et al, 2007), 16 (Tosoni et al, 2008); for reach, 2 (Pellijeff et al, 2006), 6 (Prado et al, 2005, 9 (Culham et al, 2008;Gallivan et al, 2009), 12 (Filimon et al, 2009), 13 (Beurze et al, 2007, 15 , 17 (Busan et al, 2009a,b), P3 (van Donkelaar and Adams, 2005;Vesia et al, 2006Vesia et al, , 2008Koch et al, 2008); for point, 3 (Medendorp et al, 2005), 4 (Astafiev et al, 2003), 5 (Connolly et al, 2003), 14 (DeSouza et al, 2000; for eye-hand coordination, P3 (van Donkelaar et al, 2000); for joystick, P3 (Smyrnis et al, 2003), 18 (Grefkes et al, 2004); for l...…”
Section: Goal Encoding Vs Reach Vector Encodingmentioning
confidence: 99%
“…The last 15 null-field trials were added to examine the occurrence of aftereffects. Because the effect of eye movements on reaching can be affected by stimulation over certain areas of PPC (Van Donkelaar et al, 2000), subjects were instructed to keep their eyes fixated on the target at all times. Subjects could therefore see their arm only through peripheral vision (no cursor was used to represent hand motion).…”
Section: Methodsmentioning
confidence: 99%